Customer satisfaction in the catering industry: Contrasts between Lithuania and Portugal - Lina Pilelienė; Nuno Almeida; Viktorija Grigaliūnaitė (Tourism & Management Studies)
This paper analyzes the differences between customer satisfaction in the catering industry in two different countries: Lithuania and Portugal. The adjusted European Customer Satisfaction Index is applied for the measurement of the customer satisfaction in the catering industry. Data were collected in 2014, with the aim to identify the key factors that could affect the customer satisfaction in the catering industries in these two countries. The results indicate that the determinants of customer satisfaction with catering facilities are quite similar in both countries. Eight structural relations are significant: image influences expectations and loyalty; expectations influence perceived quality; perceived quality influences perceived value and satisfaction; perceived value influences satisfaction; and satisfaction influences loyalty and complaints. Three statistically non-significant direct causal relations are presented: complaints do not influence loyalty; expectations do not influence perceived value as well as satisfaction. Only one country-specific relation is detected: the effect of image on satisfaction is statistically significant only for Portuguese consumers.